Focal mechanisms of felt earthquakes in Costa Rica during 2024 - Linkimer, Lepolt (2025)
This study presents 139 new focal mechanisms calculated in the context of the annual seismicity review of 2024. In total, the National Seismological Network (RSN) located 5378 events, whose combined energy is equivalent to an earthquake of moment magnitude (Mw) 6.6. Only ~3.8 % (204) of the earthquakes were perceived by the population. The focal mechanisms and locations of these events allowed the earthquake source to be grouped into five categories: faulting in the Caribbean and Panama upper plates, interplate seismogenic zone of the Cocos plate, internal deformation of the subducted Cocos plate, faulting in the boundary between the Cocos and Nazca plates, and faulting in the Cocos plate prior to subduction. The shallow (< 35 km) earthquakes in the upper-plates and in the Coco-Nazca boundary occurred mainly on strike-slip faults, while those related to subduction were reverse. The ten most significant earthquakes felt in 2024 reached magnitudes of Mw 5.5-6.2. The maximum intensity was V, observed in very small areas near the epicenters of six earthquakes (Mw 4.9 and 6.2).